Morphological variations in the basioccipital region of the South Indian skull - Ray, B; Kalthur, SG; Kumar, B; Bhat, MRK; D'souza, AS; Gulati, HS; KN, LK; VS, B (Nepal Journal of Medical Sciences, 2015)
Background: The craniovertebral junction is a transitional region of spine that exhibits extensive structural variability. Variations of basiocciput are of interest for anatomists and clinicians because they produce clinical symptoms or lead to misinterpretations of radiological images. Materials and Methods: The study was conducted on 202 dry human skull bone (12 occipital bone and crania 190) belonging to south Indian population for variations of basiocciput over a period of six years. Results: Prevalence of hyperostotic variants was significantly higher than hypostotic variants in present study. Most common type observed was of precondylar tubercle (2.48%) followed by fossa navicularis (1.49). The prevalence of other variations such as prebasioccipital arch, third occipital condyle, exostosis and basioccipital cleft was similar (0.5%) in the study population. Conclusions: These cranio-vertebral anomalies will be useful not only to anatomists, radiologists and surgeons while dealing with base of the skull and basiocciput in particular but also to study anthropological significance and may guide the future researchers in comparative human anatomy. Nepal Journal of Medical Sciences Vol.3(2) 2014: 124-128